DEPENDENCE OF FLEXIBILITY AND CARRYING CAPACITY SZHATYHZHELEZOBETONNYH PROFILES OF VARIOUS FACTORS - and and (Municipal economy of cities (Technical science), 2013)
The question of central and eccentrically compressed reinforced concrete cores, analyzed the nature of the deformable The influence of eccentricity value of load on the nature of the deformation of the rod.